Leaching of heavy metals from abandoned mine tailings brought by precipitation and the associated environmental impact - Wang, Ping; Sun, Zehang; Hu, Yuanan; Cheng, Hefa (The Science of the total environment, 2019)
Abandoned tailings are one of the most important sources of heavy metal pollution in the areas surrounding mining districts, and significant leaching of heavy metals could be brought by precipitation. This study investigated the leaching of heavy metals from the tailings of a small-scale abandoned polymetallic mine in south China by rainwater with batch and column tests and evaluated the associated environmental impact. The mean contents of Cr, Ni, Cu, Zn, As, Cd, and Pb in the un-weathered mine tailings were 1.46×102, 3.11×102, 4.10×103, 2.18×104, 2.82×102, 5.65×102, and 8.74×103mg/kg, respectively, and appreciable fractions of Cd, Zn, Cu, and Cr in the tailings were present in the acid soluble form. Batch and column leaching tests consistently showed that significant quantities of heavy metals could be released from the mine tailings. Based on the results of column leaching tests, it was estimated that the average fluxes of Cr, Ni, Cu, Zn, As, Cd, and Pb from the mine tailings at the studied mining district leached by precipitation were 3.20, 38.3, 12.5, 1.52×104, 104, 1.08, and 9.26g/ha/yr, respectively. The metal-rich tailing leachate would impact the quality of surface water and soils downhill of the mining district, and pose significant potential ecological risk to the farmland soils, which are irrigated by local surface water. These findings indicate the importance of tailings as a source of heavy metals in the mining districts of south China with heavy precipitation, as well as the need for mitigating the releases of heavy metals and the associated environmental impact from abandoned mine tailings. [Display omitted] •Mine tailings are an important source of heavy metals to the surrounding environment•Leaching of heavy metals from mine tailings was studied with batch and column tests•>5% of Cd and Zn, >1% of Cu and Cr in the tailings were present in acid soluble form•Rainwater could leach significant quantities of heavy metals from the mine tailings•Leachate from mine tailings could cause accumulation of heavy metals in local soils